Fermentation of pineapple juice with Lactiplantibacillus plantarum subsp. plantarum Dad-13: Sensory and microbiological characteristics - Aziz, Fariz Nurmita; Utami, Tyas; Suroto, Dian Anggraini; Yanti, Rini; Rahayu, Endang Sutriswati (Czech Academy of Agricultural Sciences, 2023)
Among the varieties of pineapples, honey pineapple is suitable to be processed as a probiotic beverage. The study aimed to evaluate the honey pineapple juice as a growth medium for Lactiplantibacillus plantarum subsp. plantarum Dad-13 probiotic strain. The pineapple juice was fermented by adding a starter culture of L. plantarum Dad-13. The fermentation time (0, 4, 8, 12, 16, 20, and 24 h) was used as a variable. The number of L. plantarum Dad-13 cells increased significantly after fermentation (P < 0.05). In acidic pineapple juice L. plantarum Dad-13 can still grow more than 2 log cycles. After 16 h, the results showed the best characteristics with cell count (8.86 log CFUÂ·mLâ1), pH (3.52), and titratable acidity (0.59). To balance the sour taste, the 8 sucrose addition was the most preferred by the panellists (n = 67), with a 5.74 (slightly like) overall acceptance score. After 42 days, there was no significant decrease in cell viability. The number of cells on day 42 was 8.81 log CFUÂ·mLâ1 with significant changes in pH and titratable acidity. The study showed that honey pineapple juice is a suitable growth medium for L. plantarum Dad-13. Â© The authors. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International (CC BY-NC 4.0).